Wall motion assessment by feature tracking in pediatric patients with coronary anomalies undergoing dobutamine stress CMR - Sachdeva, Shagun; Molossi, Silvana; Reaves-O’Neal, Dana; Masand, Prakash; Doan, Tam T. (Frontiers in Cardiovascular Medicine, 2024)
Background: Left ventricular (LV) wall motion assessment is an important adjunct in addition to perfusion defects in assessing ischemic changes. Our aim is to study the feasibility and utility of performing feature tracking (FT) in pediatric patients with coronary anomalies undergoing dobutamine stress CMR to assess wall motion abnormalities (WMA) and perfusion defects.Retrospective study where ten patients with an inducible first pass perfusion (FPP) defect and 10 without were selected. Global LV circumferential strain/strain rate (GCS/GCSR) were measured at rest and at peak stress (systole and diastole) using a commercially available feature tracking software. Peak GCS and GCSR were compared to indexed wall motion score (WMSI), between groups with and without FPP defect, and in subjects with and without WMA.Results: Patients median age was 13.5 years (11,15). Five subjects had qualitatively WMA at peak stress. Moderate correlation of GCS with WMSI at peak stress (0.48, p=0.026) and significant difference between GCS at rest and stress in patients with no inducible WMA (p=0.007) were seen. No significant difference noted in GCS between rest and stress in patients with WMA (p=0.13). There was larger absolute GCS/GCSR at peak stress in subjects with no inducible FPP defect or WMA.Smaller absolute GCS, as well as lack of significant change in GCS at peak stress in those with inducible WMA or perfusion defect, is suggestive of compromised LV deformation in subjects with inducible WMA. Given these findings, GCS derived from CMR-FT may be used to objectively assess WMA in pediatric patients undergoing stress CMR.-anomalous origin of the right coronary artery AAOLCA -anomalous origin of the left coronary artery CA -Coronary anomalies DSCMR -Cardiovascular magnetic resonance with dobutamine stress CMR-FT -Cardiac magnetic resonance imaging myocardial feature tracking FPP -first pass perfusion GCS -Global LV circumferential strain GCSR -Global LV circumferential strain rate LV -Left ventricular WMA -wall motion abnormalities MB -myocardial bridge WMSI -Wall motion score index